2022
DOI: 10.1093/biomethods/bpac002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a community-based intervention (Konga model) to address the factors contributing to viral load suppression among children living with HIV in Tanzania: a cluster-randomized clinical trial protocol

Abstract: This study aims to test the effectiveness of a community-based intervention (Konga model) to improve viral-load suppression in children living with human immunodeficiency virus (HIV) and enrolled in care and treatment centers in Tanzania mainland. The study will be a cluster-randomized clinical trial study designed with both intervention and control arms. The study will involve 268 children with a viral load of > 1,000 copies/mLwho are aged between 2 and 14 years. The children will be randomly allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Extant evidence from the United Nations Programme on HIV/AIDS (UNAIDS), shows that, the overall VLS among children living with HIV (CLHIV) aged 0-14 years, was 47% in 2020 (2). Trials in different countries have demonstrated that community-based intervention improves HIV care services among children living with HIV and AIDS (10). However, in Tanzania there has been limited documentation of the contribution of community-based interventions on improving health outcomes of children living with HIV who are on-ART (11).…”
Section: Resultsmentioning
confidence: 99%
“…Extant evidence from the United Nations Programme on HIV/AIDS (UNAIDS), shows that, the overall VLS among children living with HIV (CLHIV) aged 0-14 years, was 47% in 2020 (2). Trials in different countries have demonstrated that community-based intervention improves HIV care services among children living with HIV and AIDS (10). However, in Tanzania there has been limited documentation of the contribution of community-based interventions on improving health outcomes of children living with HIV who are on-ART (11).…”
Section: Resultsmentioning
confidence: 99%
“…The data presented in this article were collected from children with high VLs >6 months after ART initiation. The raw data are a set of demographic and clinical characteristics of children and are shared publicly in Figshare [7] . The data descriptor ( Table 1 ) is provided with the shared dataset.…”
Section: Data Descriptionmentioning
confidence: 99%